Myanmar Economic Monitor, May 2018 : Growth Amidst Uncertainty - World Bank Group (World Bank, Washington, DC, 2018)
Myanmar's economy performed better in 2017/18 with a modest growth acceleration that partially reversed the deterioration experienced in 2016/17. While the outlook remains positive, risks have intensified. The economy experienced a broad-based increase in real GDP growth to 6.4 percent in 2017/181 from 5.9 percent in 2016/17. Inflation moderated from 7 percent in 2016/17 to 5.5 percent in 2017/18. The exchange rate was stable and appreciated slightly towards the end of the year, the current account deficit narrowed slightly on strong export growth, and the fiscal deficit also narrowed in the first three quarters of the fiscal year. While performance remains strong and the macroeconomic outlook is positive, there are concerns that the slow pace of reforms, vulnerabilities in the financial sector, and limited progress in addressing the humanitarian crisis in Rakhine are starting to affect business sentiment and could weaken performance. External risks from uncertainty in global trade policy and in commodity prices intensify the downside risks to the growth outlook.